Adsorption of two gas molecules at a single metal site in a metal–organic framework. Issue 53 (10th June 2016) - Runčevski, Tomče; Kapelewski, Matthew T.; Torres-Gavosto, Rodolfo M.; Tarver, Jacob D.; Brown, Craig M.; Long, Jeffrey R.
Abstract : One strategy to markedly increase the gas storage capacity of metal–organic frameworks is to introduce coordinatively-unsaturated metal centers capable of binding multiple gas molecules. Abstract : One strategy to markedly increase the gas storage capacity of metal–organic frameworks is to introduce coordinatively-unsaturated metal centers capable of binding multiple gas molecules. Herein, we provide an initial demonstration that a single metal site within a framework can support the terminal coordination of two gas molecules—specifically hydrogen, methane, or carbon dioxide.